A Correlational Study on Architectural Design and Thermal Distribution Patterns Using a Novel Multi-Terminal Approach in Cylindrical Li-Ion Cell-Integrated Battery Packs - Sagar D; Raja Ramar; Shama Ravichandran (World Electric Vehicle Journal)
A novel architectural design is proposed to mitigate uneven thermal distribution, peak temperature, and heat spot generation, which are common issues that are observed in conventional battery packs. This approach features a multi-terminal configuration, incorporating a modified battery pack structure along with a multi-terminal switching algorithm that identifies the optimal terminal for current flow to the load. In the proposed design, the first and second terminals are placed at the first and fourth series string while the battery pack is divided into four regions, each corresponding to one series string. Additionally, terminal points represent the four thermal zones at the pack level. Experiments were conducted to evaluate the performance of the dual-terminal switching mechanism in three configurations—1S, 2S, and 3S. The 1S setup outperformed the single-terminal design, achieving a 6.23% improvement in reducing the zone temperature difference (ΔPz). The 2S configuration demonstrated an 11.11% improvement, while the 3S setup achieved an improvement in peak region difference (ΔPr) of >50%, without a cooling system. Finally, while forced air cooling effectively lowers peak temperature, it is insufficient in addressing thermal distribution and heat spot formation. However, integrating the proposed multi-terminal approach enables the effective control and management of all three critical thermal parameters—peak temperature, thermal distribution, and heat spot generation.